Development of GIS-Based Oil Spill Detection and Monitoring System - Tee, Tuan Poy (2000)
Geographical Information System (GIS) and remote sensing technologies were used to develop a GIS-based Oil Spill Detection and Monitoring System in this study. The system can be used to manage, identify, and predict oil movement when there is an incident of oil spill. Historical oil spill data, accessibility of response team's information and prevention/protection methods were established and placed in GIS for rapid access, retrieval and query. However, the archive remotely sensed data from SPOT Panchromatic, SPOT XS, NOAA AVHRR, and Landsat TM were analysed to identify and derive valuable information such as location, quantity, and distribution of oil spill in the affected area. A simple oil trajectory model was incorporated into GIS context to predict the slick movement's magnitude and direction. The developed GIS database contained over 15 layers of oil spill and coastal data. These data could be applied for mapping, overlay, classification, and integration analysis. As more data were collected, new layers could be produced, stored, and updated. The oil slick could be identified from the SPOT Panchromatic and SPOT XS. Three criterias used to identify the oil slick were the location of incidence, size of the spill and the reflectance verification. Oil prediction trajectory showed a good predicted direction of slick movement on panchromatic image. In contrast, the SPOT XS result indicated the oil impinged on the shoreline before the image was captured. The GIS-based system can be used to establish the appropriate response to locate the dense areas of slicks and for local surveillance, in order to permit clean-up vessels to detect the oil to be cleared rapidly. Also, it allows new opportunities for multiple resource planning, and permits the viewing of a state's natural resources. Therefore, the GIS-based system can consequently improve the decision-making process, and provide a baseline for future assessments.